Suporte para transmissão de mídia contínua entre servidor e clientes cooperativos - Shimoda, Marcio Akio (Universidade Federal de São Carlos, 2005)
In this work the problem of the multimedia content distribution to a large number of computers is addressed. Specifically, we consider the problem of the server overloading that occurs due to the increase of the volume of requests to receive content. The consequence is the increase of response time and denial of service. As solution a communication model complementing the traditional client-serve is presented. It is based on the cooperative networks, where the clients cooperate to distribute the media, where they act as a kind of temporary server, until the server come back to a normal stage. Using such redirectioning scheme, the data networked traffic on server is decreased which alleviates its load. The proposed solution is shown in detail, pointing the modifications in the traditional model.
Keywords: Sistemas distribuídos; Peer-to-peer; Distribuição de mídia; Media distribution; Peer-to-peer; Cooperative clients; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO